Guramata hulāsa : janama toṃ leke anta prayanta gurabāṇī anusāra singhāṃ de kāraja karana dī bidhī - Ṭhākara Siṅgha (SAMP early 20th-century Indian books project ;, 1898)
On Sikh social and religious rituals.